Five-minute activities a resource book of short activities - Ur, Penny; Wright, Andrew 1937- (Cambridge University Press, 1992)
Five Minute Activities is a collection of over 100 ideas for the foreign language classroom, all of which can be used effectively with little or no preparation. The collection offers a convenient reference for established activities and an introduction to a large number of new ones. The activities can vary pace and content, provide transitions, and otherwise contribute to the "well-orchestrated" lesson; give an opportunity for brief review and practice of vocabulary or grammar; help students and teacher to get to know each other; and offer extra material when a teacher has to fill in for a colleague at short notice. Though many of the activities are enjoyable and game-like, they are not mere "fillers" but genuine language-learning procedures, whose use can contribute significantly to the learning value of lessons and to the interest and enjoyment of students. The activities can be used at various levels of proficiency.